Peradaban Islam Masa Khalifah Umar Bin Khattab - Muhammad Basri; Nayla Rizka Irwani; Nurhayati Nurhayati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Umar ibn Khattab was a resolute and courageous leader. Traits of justice, generosity, high spirit of struggle, intelligence, and strong faith were ingrained in the personality of Umar ibn Khattab. Before embracing Islam, Umar himself belonged to a prestigious lineage among the Quraysh. Umar ibn Khattab's leadership earned him the title of Amirul Mukminin, while the state he led was referred to as a caliphate. This is utilize literary resources such as books, journals, and various written works for referencing purpose.s Khalifah Umar was an excellent administrator, as evidenced by his actions since assuming power. The first task undertaken by Khalifah Umar was the establishment of the Hijri calendar.